Pengaruh Profitabilitas, Kinerja Keuangan, Struktur Modal Terhadap Harga Saham Syariah - Mohammad Derry Yalbuk Ramadhan; Lembah Dewi Andini (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2022)
This study aims to determine the effect of profitability, financial performance, capital structure on sharia stock prices. The Independent variables in this study are profitability, financial performance and capital structure. The dependent variable is the Islamic stock price. The research method uses quantitative methods. The population in this study are companies registered in the Jakarta Islamic Index (JII) during 2015-2019. The research sample of this study were 14 companies listed on the Jakarta Islamic Index obtained by purposive sampling. The analysis technique used in this study is multiple linear regression. The results showed that profitability had a significant effect on sharia stock prices, financial performance had a significant effect on sharia stock prices and capital structure had a significant effect but negative on sharia stock prices.